Practical considerations will ensure the continued success of pre-harvest biocontrol using non-aflatoxigenic Aspergillus flavus strains. Issue 15 (13th May 2022) - Moore, Geromy G.
Abstract: There is an important reason for the accelerated use of non-aflatoxigenic Aspergillus flavus to mitigate pre-harvest aflatoxin contamination… it effectively addresses the imperative need for safer food and feed. Now that we have decades of proof of the effectiveness of A. flavus as biocontrol, it is time to improve several aspects of this strategy. If we are to continue relying heavily on this form of aflatoxin mitigation, there are considerations we must acknowledge, and actions we must take, to ensure that we are best wielding this strategy to our advantage. These include its: (1) potential to produce other mycotoxins, (2) persistence in the field in light of several ecological factors, (3) its reproductive and genetic stability, (4) the mechanism(s) employed that allow it to elicit control over aflatoxigenic strains and species of agricultural importance and (5) supplemental alternatives that increase its effectiveness. There is a need to be consistent, practical and thoughtful when it comes to implementing this method of mycotoxin mitigation since these fungi are living organisms that have been adapting, evolving and surviving on this planet for tens-of-millions of years. This document will serve as a critical review of the literature regarding pre-harvest A. flavus biocontrol and will discuss opportunities for improvements.